Five new cases of breast cancer in transsexual persons. (22nd January 2015) - Gooren, L.; Bowers, M.; Lips, P.; Konings, I. R.
Summary: Cross‐sex hormone treatment of transsexual people may be associated with the induction and growth stimulation of hormone‐related malignancies. We report here five cases of breast cancer, three in female‐to‐male (FtoM) transsexual subjects and two in male‐to‐female (MtoF) transsexual subjects. In the general population the incidence of breast cancer increases with age and with duration of exposure to sex hormones. This pattern was not recognised in these five transsexual subjects. Tumours occurred at a relatively young age (respectively, 48, 41, 41, 52 and 46 years old) and mostly after a relatively short span of time of cross‐sex hormone treatment (9, 9–10 but in one after 30 years). Occurrence of breast cancer was rare. As has been reported earlier, breast tumours may occur in residual mammary tissue after breast ablation in FtoM transsexual people. For adequate treatment and decisions on further cross‐sex hormone treatment it is important to have information on the staging and histology of the breast tumour (type, grade and receptor status), with an upcoming role for the androgen receptor status, especially in FtoM transsexual subjects with breast cancer who receive testosterone administration. This information should be taken into account when considering further cross‐sex hormone treatment.